INDONESIA’S REGULATION AND POLICY IN THE ENERGY SECTOR: URGENCY TO PROMOTE ENERGY EFFICIENCY IN URBAN AREAS - Mulyana, Imam; Siswandi, Achmad Gusman (Yustisia, 2018)
In recent years, efforts to promote sustainable energy through energy efficiency, renewable energy and use of new technologies are moving rapidly at national, regional, and international levels. The benefits generated from energy efficiency has prompted experts and governments to work together in implementing energy efficiency policies across all sectors of life. One of the focus areas in global energy efficiency policy is energy efficiency in urban areas. This article aims to provide an overview regarding the implementation of policy and regulation on energy efficiency in Indonesia, particularly in urban areas. The research finds that energy efficiency is one of the most effective ways to improve the competitiveness and capacity of cities in Indonesia. In addition, it could advocate the Indonesian Government in responding to global environmental issues, especially climate change.